Nonlinear Time-History Evaluation of Interstory Lead Rubber Bearing (LRB) Isolation in Reinforced Concrete Buildings - Angela Ayu Putri; Josia Irwan Rastandi; Jessica Sjah (G-Tech: Jurnal Teknologi Terapan, 2026)
Seismic isolation is widely recognized as an effective strategy for mitigating earthquake-induced structural response. However, most studies have focused on base-isolated systems, whereas interstory isolation remains less explored. In particular, research on interstory LRB isolation for multistory reinforced concrete buildings in Indonesia remains limited. This study investigates a 13-story reinforced concrete dual-system building equipped with interstory Lead Rubber Bearing (LRB) isolators between the first and second floors. Two configurations are considered: fixed-base and interstory-isolated models. Seismic performance is evaluated through nonlinear time-history analysis using eleven ground-motion record pairs selected to represent Indonesian seismic hazard conditions, with nonlinear behavior considered for the isolators and critical ground-story elements. This study contributes to the limited research on interstory LRB isolation by clarifying how seismic demands are redistributed in a dual RC building under Indonesian hazard-consistent ground motions. Results show that interstory LRB isolation elongates the fundamental period from 0.91–1.51 s to 2.64–2.94 s, reduces base shear by 32–37%, decreases overturning moment by 71–78%, and lowers maximum interstory drift ratio from 1.87% to 0.52% in X and from 2.48% to 0.87% in Y. These results demonstrate that interstory LRB isolation is a promising alternative when conventional base isolation is impractical.